Frontispiece: A Supported Nickel Catalyst Stabilized by a Surface Digging Effect for Efficient Methane Oxidation. Issue 51 (9th December 2019) - Zhou, Huang; Liu, Tianyang; Zhao, Xuyan; Zhao, Yafei; Lv, Hongwei; Fang, Shi; Wang, Xiaoqian; Zhou, Fangyao; Xu, Qian; Xu, Jie; Xiong, Can; Xue, Zhenggang; et al.
Abstract : Methane Oxidation In their Communication on page 18388, J. Luo, Y. Li, Y. Wu et al. present Ni NPs that etch and sink into a N‐doped carbon support to prevent sintering. The Ni NPs are transformed into metal‐defect sites in C−H bond activation for methane oxidation by elevating the temperature.